Hybrid, ambiguous, and non-linear? How new is Russia's 'new way of war'?. (3rd March 2016) - Galeotti, Mark
Abstract: Russia's recent operations in Ukraine, especially the integrated use of militias, gangsters, information operations, intelligence, and special forces, have created a concern in the West about a 'new way of war', sometimes described as 'hybrid'. However, not only are many of the tactics used familiar from Western operations, they also have their roots in Soviet and pre-Soviet Russian practice. They are distinctive in terms of the degree to which they are willing to give primacy to 'non-kinetic' means, the scale of integration of non-state actors, and tight linkage between political and military command structures. However, this is all largely a question of degree rather than true qualitative novelty. Instead, what is new is the contemporary political, military, technological, and social context in which new wars are being fought.